2021
DOI: 10.3390/microorganisms9020318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ceftiofur Administration in Steers on the Prevalence and Antimicrobial Resistance of Campylobacter spp.

Abstract: Bacterial resistance to ceftiofur raises health concerns due to ceftiofur’s extensive veterinary usage and structural similarity with the human antibiotic ceftriaxone. Ceftiofur crystalline-free acid (CCFA) and ceftiofur hydrochloride (CHCL) are ceftiofur types used therapeutically in cattle, but their potential impacts on Campylobacter prevalence and antimicrobial resistance remain unclear. In this study two groups of steers were each treated with CCFA or CHCL. In vivo active drug concentrations were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…This suggests that new alleles detected only at one temperature are more likely to be encountered in strains isolated at 42 • C. Neighbor-net SplitsTree analysis based on wgMLST showed that the five ST8221 strains were closely related, as were the six strains of ST8567, with a large distance between the two STs (Figure 4A). This agrees with the previous finding that ST8221 and ST8567 were both novel STs and only shared one allele in the seven-locus MLST scheme [9]. In spite of the close relatedness among the ST8221 strains, however, those isolated at 42 • C tended to exhibit higher variation (Figure 4B), with similar findings for the strains of ST8567 (Figure 4C).…”
supporting
confidence: 91%
See 4 more Smart Citations
“…This suggests that new alleles detected only at one temperature are more likely to be encountered in strains isolated at 42 • C. Neighbor-net SplitsTree analysis based on wgMLST showed that the five ST8221 strains were closely related, as were the six strains of ST8567, with a large distance between the two STs (Figure 4A). This agrees with the previous finding that ST8221 and ST8567 were both novel STs and only shared one allele in the seven-locus MLST scheme [9]. In spite of the close relatedness among the ST8221 strains, however, those isolated at 42 • C tended to exhibit higher variation (Figure 4B), with similar findings for the strains of ST8567 (Figure 4C).…”
supporting
confidence: 91%
“…The 18 C. jejuni strains that were selected to examine the temperature impact on the genome sequence were isolated during our previous study that assessed the effect of ceftiofur treatment of steers on Campylobacter [9]. All strains were isolated as previously described by selective enrichments of the fecal samples in Bolton broth at 37 • C following by plating of 0.1 mL of the enrichment on mCCDA plates that were incubated at 37 • C or 42 • C [9]. The strain panel included eight paired strains, i.e., one strain that had been isolated on mCCDA at 37 • C and another isolated on mCCDA at 42 • C from each of the four fecal samples.…”
Section: Jejuni Strains and Culture Conditionsmentioning
confidence: 99%
See 3 more Smart Citations